A prática do tutor na mediação do conhecimento com o aluno do curso de Filosofia a distância da UEMA - PRAZERES, Girsivania Teixeira dos (2015)
Practice analysis tutor distance of UEMA Philosophy Course as a mediator of knowledge. This work is presented as an investigation of the practice of an important educational subject Education modality of distance (distance education), the so-called 'education tutor at distance', which is justified by its action deemed essential to the process of teaching and learning this sport education. Thus, the general objective of this research was to investigate the practice of tutor distance of Philosophy Course at the State University of Maranhão as meidation of knowledge, with the possibility of forming a student autonomy. Therefore we support you in the literature of distance education of authors such as João Mattar, Daniel Mill, as well as the MEC (Ministry of Education and Culture) Quality Benchmarks that addresses the quality of distance education. In theoretical foundation, through literature review of hermeneutical nature, authors used the philosphy as Walter Benjamin and Theodor Adorno to address the issue of educational autonomy, as libertarian practice consistent with the possibility of student training within the context of media and communication tools mass of modernity. About investigative practice, it is a case study in the course of Philosophy Degree of UEMA. To carry out the research we use questionnaires with closed and open questions as research tools applied to tutors and students of that course, and surveys data were through statistical methods for closed-ended questions and content analysis to the open questions. The importance of mentoring practice observed by tutors and students investigated, where both groups pointed to the mediation of knowledge involved in the formation of autonomy as concrete and observed reality is concluded. Therefore, there have been new study perspectives related to education and its emancipatory role.